Islamic Legal Perspective on the 'Macelleng-Celleng' Tradition in the Marriage Process (IAIN Parepare, 2023)
This research aims to determine the implementation of maccelleng-celleng in the marriage process of the people of Segeri District, Pangkep Regency, to find out what factors cause the maintenance of the maccelleng-celleng tradition in Segeri District, Pangkep Regency, and to find out the Islamic law review of the maccelleng-celleng traditional tradition in Segeri District, Regency. Pangkep. This research is field research using qualitative methods, with a phenomenological approach, namely an approach that will explore data to find the meaning of basic and essential things from phenomena, realities or experiences experienced by the object of research. This research uses observation research, interviews and documentation. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results of this research show that the implementation of the macelleng-celleng tradition is a habit of the people of Segeri District, Pangkep Regency, before the wedding ceremony. This tradition is carried out at night, and the groom's family brings snacks such as instant noodles, soap, crackers, and so on. To be taken to the prospective bride's house by throwing it. The development of the macelleng-celleng tradition is growing very quickly with the help of the people of Segeri District, Pangkep Regency in introducing this tradition to people from outside the Pangkep Regency area. The development of the macelleng-celleng tradition has of course existed since ancient times, and is still preserved by the people of Segeri subdistrict, Pangkep district to this day. Based on the author's findings, the macelleng-celleng tradition, if viewed in Islamic law, is that if this tradition is carried out in accordance with the rules and does not violate Islamic norms or values, then this macelleng-celleng tradition can be implemented according to the applicable rules.